Effects of tributyltin on placental and reproductive abnormalities in offspring - Charles S. da Costa; Hanin Alahmadi; Genoa R. Warner; Maria Tereza Nunes; Glaecir Roseni Mundstock Dias; Leandro Miranda-Alves; Jones B. Graceli (Archives of Endocrinology and Metabolism)
ABSTRACT Tributyltin (TBT) is an organotin compound and a common persistent environmental pollutant with endocrine-disrupting chemical (EDC) actions. It can accumulate in the environment at various concentrations throughout the food chain in the ecosystem, posing a risk to human health, especially during critical periods such as gestation and fetal and offspring development. In this review, we report the results of studies describing the consequences of TBT exposure on placental and reproductive parameters in offspring of both sexes. Results from in vivo and in vitro studies clearly indicate that TBT causes adverse effects on placental development and reproductive parameters in offspring. However, substantial knowledge gaps remain in the literature, requiring further research to better understand the mechanisms behind TBT effects on placental and reproductive disruption in offspring.